Effect of Row Spacing in the Period Prior to Weed Interference in Peanut Cultivation Under Azorean Conditions - Parreira, Mariana Casari; Costa, Vasco Rafael Rodrigues; Lopes, David João Horta; de Portugal e Vasconcelos, João Martim; da Silva Madruga, João; Benedito, Vitor Adriano [UNESP]; Campalle, Arthur Nardi [UNESP]; Martins, Heytor Lemos [UNESP] (MDPI, 2025)
Peanut cultivation currently plays a minor role in Portuguese agriculture, despite the country’s favorable soil and climatic conditions. In the Azores archipelago, where agriculture is a key economic activity, peanut production has recently sparked interest among rural producers. Weeds pose a major threat to crop development, particularly for short-cycle species like peanuts. This study aimed to determine the period prior to weed interference (PPI) in peanut crops under two row spacings (40 cm and 60 cm) on São Miguel Island, Azores. Eight treatments were established—0–15, 0–30, 0–45, 0–60, 0–75, 0–90 days after emergence (DAE), full-season coexistence, and a weed-free control—to represent increasing periods of weed competition. A randomized block design with four replicates was used for each spacing. The weed community included eight species, with Cyperus spp., Digitaria spp., Amaranthus blitum, and Portulaca oleracea being the most prevalent. Weed interference throughout the entire cycle led to yield losses exceeding 81% and 86% at 40 cm and 60 cm row spacings, respectively. The PPI was defined at a 5% yield reduction threshold, which is a commonly accepted benchmark in weed science to determine the beginning of the critical period of weed interference.